Case report: Primary intraosseous meningioma: a radiological study of two cases confirmed pathologically - Wang, Yue; Hu, Jibo (Frontiers in Oncology, 2025)
IntroductionPrimary intraosseous meningioma (PIM) is a rare lesion often misidentified preoperatively due to its ambiguous benign or malignant characteristics. In this report, we introduce two novel cases of PIM and explore the potential correlation between pathological classification and imaging features. Our aim is to enhance our understanding of PIM and improve its preoperative diagnosis.Case presentationThe first case is a 68-year-old female patient presenting with a brain mass located in the temporal region. Computed tomography (CT) imaging demonstrated the destruction of adjacent bone structures. A right frontal temporal craniectomy was subsequently performed and histological examination pathologically confirmed the lesion was the chordoid variant of PIM. The second case is a 56-year-old male patient who exhibited an irregular soft-tissue mass in the right sphenoid as visualized on brain CT. The patient underwent a surgical intervention for a skull base neoplasm. Postoperative pathological analysis confirmed the presence of the meningothelial variant of PIM. Upon pathological examination, the two cases were respectively classified as atypical meningioma (Grade II) and benign meningioma (Grade I).ConclusionsWhile pathological examination remains indispensable for the definitive confirmation of PIM, the early identification of PIM is critically dependent on radiological imaging methods. The imaging characteristics of PIM exhibit variability across different pathological grades, a factor that can significantly aid in both the diagnostic process and the formulation of appropriate treatment strategies.